2021
DOI: 10.3390/ijerph182111104
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors, Leisure Activities, and Satisfaction during the COVID-19 Pandemic: A Cross-Sectional Study in Eleven Spanish-Speaking Countries

Abstract: The COVID-19 pandemic has affected the lives of millions of people worldwide. This study aimed to analyze the effects of several psychological factors (self-esteem, self-control, and emotional stability) over lifestyle-related variables (time spent on leisure activities) and the levels of satisfaction (family, friends, work, and leisure satisfaction) experienced during the COVID-19 outbreak. Data for this article were retrieved as part of a cross-sectional international study conducted in eleven Spanish-speaki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…The results of this study corroborated with the view of Zamani Sani et al (2016) who concluded that self-esteem significantly predicted how much time people spent engaging in leisure activities like sports and other hobbies while negatively predicting how much time was spent engaging in leisure activities like using social media and watching TV shows and videos. The results of this study also corroborated with the view of Hidalgo-Andrade, et al (2021) who concluded in their findings that self-esteem is a significant psychological element that contributes to achieving fulfillment in leisure activities.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study corroborated with the view of Zamani Sani et al (2016) who concluded that self-esteem significantly predicted how much time people spent engaging in leisure activities like sports and other hobbies while negatively predicting how much time was spent engaging in leisure activities like using social media and watching TV shows and videos. The results of this study also corroborated with the view of Hidalgo-Andrade, et al (2021) who concluded in their findings that self-esteem is a significant psychological element that contributes to achieving fulfillment in leisure activities.…”
Section: Discussionsupporting
confidence: 90%